The newfound faces of historical personalities. There can be put an end - Abroskin, V.N.; Redkina, M.G. (Perm Federal Research Centre Journal, 2024)
This article, as well as our previous ones («Vestnik of the Perm Federal Research Center» №3, 2021, and №3, 2022, and №4, 2023), is devoted to the 110th anniversary of the visit of Grand Duchess Elizabeth Feodorovna and her sister Princess Victoria von Battenberg to the city of Perm and Perm govenorate on the eve of the First World War, in July 1914. The article completes our investigation on photo-identification of historical personalities depicted on the group photo in the garden of the Governor’ house. The Governor I.F. Koshko took most active and direct part in receiving the distinguished guests on Perm land. Our final material is devoted to the first man on the right, designated as «A.P. Kornilov». For the first time we also give information concerning the hitherto unknown person who took this photograph